Efficacy of a minimal home-based psychoeducative intervention versus usual care for managing anxiety and dyspnoea in patients with severe chronic obstructive pulmonary disease: a randomised controlled trial protocol. Issue 7 (7th July 2015) - Bove, Dorthe Gaby; Overgaard, Dorthe; Lomborg, Kirsten; Lindhardt, Bjarne Ørskov; Midtgaard, Julie
Abstract : Introduction: In its final stages, chronic obstructive pulmonary disease is a severely disabling condition that is characterised by dyspnoea, which causes substantial anxiety. Anxiety is associated with an impaired quality of life and increased hospital admissions. Untreated comorbid anxiety can have devastating consequences for both patients and their relatives. Non-pharmacological interventions, including cognitive–behavioural therapy, have been effective in managing anxiety and dyspnoea in patients with chronic obstructive pulmonary disease. However, the majority of existing interventions have tested the efficacy of relatively intensive comprehensive programmes and primarily targeted patients who have moderate pulmonary disease. We present the rationale and design for a trial that focused on addressing the challenges experienced by severe pulmonary disease populations. The trial investigates the efficacy of a minimal home-based psychoeducative intervention versus usual care for patients with severe chronic obstructive pulmonary disease. Methods and analysis: The trial is a randomised controlled trial with a 4-week and 3-month follow-up. 66 patients with severe chronic obstructive pulmonary disease and associated anxiety will be randomised 1:1 to either an intervention or control group. The intervention consists of a single psychoeducative session in the patient's home in combination with a telephone booster session. The intervention is based on a manual, with a theoretical foundation in cognitive–behavioural therapy and psychoeducation. The primary outcome is patient-reported anxiety as assessed by the Hospital and Anxiety and Depression Scale (HADS). Ethics and dissemination: This trial complies with the latest Declaration of Helsinki, and The Ethics Committee of the Capital Region of Denmark (number H-1-2013-092) was queried for ethical approval. Trial results will be disseminated in peer-reviewed publications and presented at scientific conferences. Trial registration number: NCT02366390.